2005
DOI: 10.1002/chin.200536231
|View full text |Cite
|
Sign up to set email alerts
|

gem‐Disubstituent Effect: Theoretical Basis and Synthetic Applications

Abstract: Organic chemistry Z 0200 gem-Disubstituent Effect: Theoretical Basis and Synthetic Applications -[about 120 refs.]. -(JUNG, M. E.; PIIZZI, G.; Chem. Rev. (Washington, D. C.) 105 (2005) 5, 1735-1766; Dep. Chem. Biochem., Univ. Calif., Los Angeles, CA 90095, USA; Eng.) -Lindner 36-231

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 1 publication
2
95
0
Order By: Relevance
“…Such interactions specifically accelerate autoproteolysis with Thr when the γ-methyl forms unfavorable steric interactions in nonproductive rotamers. This reactive rotamer effect (RRE) is disrupted by the Thr → Ser mutation, which shifts the ground state rotamer distribution away from a reactive state, accounting for the entropically derived rate deceleration (29). The RRE may contribute to the previously unexplainable observation that Thr nucleophiles are rare outside of cis-autoproteolytically activated systems, but common among the Ntn and D/O hydrolases (14,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…Such interactions specifically accelerate autoproteolysis with Thr when the γ-methyl forms unfavorable steric interactions in nonproductive rotamers. This reactive rotamer effect (RRE) is disrupted by the Thr → Ser mutation, which shifts the ground state rotamer distribution away from a reactive state, accounting for the entropically derived rate deceleration (29). The RRE may contribute to the previously unexplainable observation that Thr nucleophiles are rare outside of cis-autoproteolytically activated systems, but common among the Ntn and D/O hydrolases (14,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…[ 113 ] In contrast to the previous reports [ 114‐118 ] that the dicarbofunctionalization of alkenes was restricted to the formation of five‐membered rings, this method could afford piperidine derivatives by 6‐exo‐trig cyclization. Thorpe‐Ingold effect [ 119 ] played a crucial role on the efficiency of the radical cyclization, as the unsubstituted carbochain favored direct coupling with another electronphile, such as arylbromide, prior to cyclization.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 99%
“…Replacement of the phenyl substituents with methyl groups ( 1l ) or hydrogens ( 1m ) led to a dramatic decrease in the yield of cyclization product 2l or even a complete deactivation for the formation of 2m (Scheme a). These results demonstrated that the phenyl substituents had an obvious Thorpe‐Ingold effect on the intramolecular hydroalkoxylation . Reaction of 2‐allylphenol ( 1n ) under the standard conditions did not give the corresponding cyclized hydroalkoxylation product, but produced hydrochlorination product 4 (Scheme b).…”
Section: Resultsmentioning
confidence: 94%